INNOVATIVE APPROACH IN THE PROFESSIONAL TRAINING OF MASTERS IN CYBER SECURITY - Rizak, Vasyl; Opachko, Magdalyna; Deshko, Nataliya (Physical and Mathematical Education, 2023)
Formulation of the problem. Educational programs of the second academic and professional level (master degree) of the Physics Faculty of UzhNU list competencies that are specific elements of the specialist model. Developing in future specialists the ability to adapt to work at an innovative level involves the developing, among others, of skills to innovatively solve scientific and research problems. This assumes the type of organization of specialist training, which ensures the formation of innovative thinking skills. Materials and methods. Theoretical (analysis of scientific literature on the issue under consideration and content analysis of modern trends in innovative training of engineers-researchers) and empirical (questionnaire surveys conducted with masters in cyber security) methods have been applied. In the research process, the materials of educational programs for the training of masters in cyber security at the Faculty of Physics of UzhNU have also been used. Research results. The research reveals the essence of an innovative approach to the formation of competencies of masters in cyber security. It consists of updating the content, process and result of the training in the educational environment of a higher education institution. Innovations in the content of training reflect the results of methodological reflection of relationships between the concepts of "personality", "values", "innovations" and scientific-research activity. They focus attention on the concept of "innovative thinking skills". Innovations in the process of training of future specialists are marked with the markers of "innovative educational technologies", "information and communication systems, networks, connections, technologies". Innovations in the results are aimed at updating the criteria for evaluating the indicators formed, which describe the results of training and methods of their diagnosis. Conclusions. The implementation of an innovative approach in the training of masters in cyber security involves the organization of the educational process using innovative educational technologies for the development of critical and creative thinking; skills for the solving of research problems, methods of individual self-development of masters in physics.